The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pbio.3001034
|View full text |Cite
|
Sign up to set email alerts
|

CEP290 is essential for the initiation of ciliary transition zone assembly

Abstract: Cilia play critical roles during embryonic development and adult homeostasis. Dysfunction of cilia leads to various human genetic diseases, including many caused by defects in transition zones (TZs), the “gates” of cilia. The evolutionarily conserved TZ component centrosomal protein 290 (CEP290) is the most frequently mutated human ciliopathy gene, but its roles in ciliogenesis are not completely understood. Here, we report that CEP290 plays an essential role in the initiation of TZ assembly in Drosophila. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 56 publications
3
53
0
Order By: Relevance
“…CEP290 was previously reported to be involved in cell ciliogenesis [ 33 ]. Deletion of CEP290 blocked the formation of cilia by directly recruiting DAZ and zinc finger protein 1 DZIP1 [ 34 ] or by disrupting the formation and subcellular distribution of the protein complex PCM-1 [ 35 ]. However, the biological function of CEP290 is virtually unexplored in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…CEP290 was previously reported to be involved in cell ciliogenesis [ 33 ]. Deletion of CEP290 blocked the formation of cilia by directly recruiting DAZ and zinc finger protein 1 DZIP1 [ 34 ] or by disrupting the formation and subcellular distribution of the protein complex PCM-1 [ 35 ]. However, the biological function of CEP290 is virtually unexplored in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous and compound heterozygous variants in CEP290 have earlier been reported as pathogenic in various ciliopathies, including Nephronophthisis, Joubert syndrome, Meckel syndrome, Senior-Loken syndrome, Leber congenital amaurosis and Bardet-Biedl syndrome. The role of CEP290 in ciliogenesis has been widely studied and is also known to be involved in the ciliary transport processes, regulation of the ciliary membrane composition and ATF4-mediated transcription (Shimada et al, 2017;Wu et al, 2020). Although CEP290 has never been reported in the context of LS, it is intriguing to note that mutations in INPP5E a member of the same 5'phosphatase superfamily as OCRL have been associated with Joubert syndrome itself a ciliopathy (Bielas et al, 2009;Jacoby et al, 2009;Travaglini et al, 2013) and recent studies indicated an important role for phosphoinositides in ciliary biology (Conduit and Vanhaesebroeck, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have identified several genes related to MKS, such as MKS1 , TMEM216 , TMEM67 , CEP290 , RPGRIP1L , CC2D2A , NPHP3 , TCTN2 , B9D1 , B9D2 , TMEM231 , KIF14 , and TMEM107 , and most of them encode proteins concentrated to the ciliary transition zone (TZ) ( Bergmann et al, 2016 ; Dean et al, 2016 ; Wu et al, 2020 ). The TZ is characterized by Y-shaped structures spanning from the axoneme to the ciliary membrane that functions as a barrier between the cilia components and the cytoplasmic group to regulate the material transport and signal transmission of the cilia ( Garcia-Gonzalo et al, 2011 ; Anvarian et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%